COVID-19 can lead to rapid progression of cervical intraepithelial neoplasia by dysregulating the immune system: A hypothesis. (December 2022) - Becker, Sabeth; Jonigk, Danny; Luft, Angelina; Dübbel, Lena; Werlein, Christopher; Malik, Eduard; Schild-Suhren, Meike
Abstract: COVID-19 is a multisystem disease and cause of a global pandemic. Lately, cases of disease progression of HPV-infected CIN under SARS-CoV-2 infection were reported giving rise to the hypothesis of direct virus-infection induced pro-carcinogenic effect of SARS-CoV-2. We herein present a case of rapid progression from HPV-induced CIN 2 to microinvasive carcinoma within three months under COVID-19 without direct virus infection. Histopathologic evaluation, Fluorescence-in-situ hybridization and qRT-PCR against SARS-CoV-2 RNA as well as gene expression analysis were performed from the available FFPE-tissue and accompanied by an analysis of white blood cell differential. No signs of direct SARS-CoV-2 infection or COVID-19 typical alterations of cervical tissue were found. As expected, p53 decreased in expression with progression of dysplasia, while APOBEC3A and VISTA showed a decrease in expression contrary to observations in dysplasia progression. PD-L1 was expressed consistently or increased slightly but did not show the expected strong induction of expression. DNMT1 showed an increase in expression in CIN III and a slight decrease in carcinoma, while DNMT3a is consistently expressed in CIN II and decreased in carcinoma. Blood tests after COVID-19 showed substantial reduction of lymphocytes, eosinophils, T-cells, and NK-cells. Our results hint at an indirect effect of COVID-19 on the cervical neoplasm. We conclude that the immune system might be preoccupied and exhausted by the concurring COVID-19 disease, leading to less immunological pressure on the HPV-infected cervical dysplasia enabling rapid disease progression. Further, indirect proangiogenic and proinflammatory micromilieu due to the multisystemic effects of COVID-19 might play an additional role Highlights: Fast progression of cervical dysplasia into invasive carcinoma after COVID-19 disease within three months. No sign of direct cervical infection with SARS-CoV-2. Distinct signs of exhaustion and preoccupation of the immune system under COVID-19. COVID-19 might reduce the immunological pressure on HPV-infected cervical dysplasia. COVID-19 indirectly impacts cervical dysplasia favouring disease progression.